Anti-Inflammatory Regulatory Role of Signal Transducer and Activator of Transcription 3 Phosphorylation in Regulating Hypersensitivity Responses to Echinococcus granulosus Hydatid Cyst Fluid - Li SS; Zhou JR; Wang CS; Wang JL; Li YQ; Kulaixi X; Cao LW; Batesurong B; Ye JR (Journal of Inflammation Research)
Shan-Shan Li,1,2,* Jing-Ru Zhou,3,* Chun-Sheng Wang,1,2 Jia-Ling Wang,1 Yu-Qian Li,1,2 Xilizati Kulaixi,1 Li-Wei Cao,1,2 Bayina Batesurong,1,2 Jian-Rong Ye1 1Department of Anesthesiology, The First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang Uygur Autonomous Region, 830054, People’s Republic of China; 2The First Clinical Medical College of Xinjiang Medical University, Urumqi, Xinjiang Uygur Autonomous Region, 830054, People’s Republic of China; 3Department of Anesthesiology, The Sixth Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang Uygur Autonomous Region, 830063, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian-Rong Ye, Department of Anesthesiology, The First Affiliated Hospital of Xinjiang Medical University, No. 137, Liyushan South Road, Urumqi, Xinjiang Uygur Autonomous Region, 830054, People’s Republic of China, Tel +86 18999938777, Email ywjianrongym@126.comObjective: This study aims to investigate the anti-inflammatory regulatory function of signal transducer and activator of transcription 3 (STAT3) phosphorylation in hypersensitivity responses triggered by Echinococcus granulosus hydatid cyst fluid through in vitro RBL-2H3 cell culture.Methods: RBL-2H3 cells were cultured in vitro and sensitized with immunoglobulin E (IgE), followed by intervention with STAT3 inhibitors Stattic and JSI-124. Cells were subsequently exposed to crude Echinococcus granulosus hydatid cyst fluid to induce an allergic reaction. β-Hexosaminidase (HEX) release in the cell supernatant was measured to evaluate degranulation. Apoptosis was detected using flow cytometry, and changes in phosphorylated protein levels were determined via Western Blot analysis.Results: Analysis of β-HEX release in the Echinococcus-induced IgE-mediated RBL-2H3 cell degranulation model revealed that both inhibitors effectively inhibited mast cell degranulation (P < 0.01). Apoptosis assays revealed that both inhibitors caused varying degrees of cell damage (P < 0.01), potentially leading to late-stage apoptosis.Conclusion: Immunoblotting analyses confirmed that treatment with the two inhibitors reduced STAT3 phosphorylation levels at the S727 and Y705 sites, thereby inhibiting cell degranulation and alleviating immune responses.Keywords: allergic reaction, Echinococcus granulosus hydatid cyst fluid, RBL-2H3 cells, STAT3 phosphorylation